2019
DOI: 10.1016/j.prostaglandins.2019.106364
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic and antiplatelet activity of 2-((3-(chloromethyl)benzoyl)oxy)benzoic acid

Abstract: Acetylsalicylic acid is used as a non-steroidal anti-inflammatory drugs (NSAID) and antiplatelet agents by inhibiting cyclooxygenases. However, therapy using acetylsalicylic acid could induce gastric bleeding and cause other gastrointestinal toxicity. The aim of this study was to demonstrate the synthesis of a new compound bearing salicylic acid residue namely 2-((3-(chloromethyl)benzoyl)oxy)benzoic acid, to analyze its potential as a ligand for human cyclooxygenase-2 (COX-2) receptor, to evaluate its toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…This phenomenon is commonly expressed by a highly lipophilic compound. This new compound, 3CBB, was reported to be more lipophilic (log P = 3.73) than ASA (log P = 1.21) as reported in our previous study [7]. The AUCtotal of 3CBB was found to be 66.3 ± 1.0 µg min/ml (table 3).…”
Section: Fig 3: a Typical Pharmacokinetic Profile Of 3cbb In Rat Plasupporting
confidence: 62%
See 1 more Smart Citation
“…This phenomenon is commonly expressed by a highly lipophilic compound. This new compound, 3CBB, was reported to be more lipophilic (log P = 3.73) than ASA (log P = 1.21) as reported in our previous study [7]. The AUCtotal of 3CBB was found to be 66.3 ± 1.0 µg min/ml (table 3).…”
Section: Fig 3: a Typical Pharmacokinetic Profile Of 3cbb In Rat Plasupporting
confidence: 62%
“…In our previous study, we investigated the analgesic, toxicity and antiplatelet effects of 3CBB. This study demonstrated that our new compound is more active and less toxic than ASA [7].…”
Section: Fig 1: Chemical Structure Of 3cbbmentioning
confidence: 59%
“…The data indicated that 3-CH 2 Cl has a longer elimination half-life (t 1⁄2 = 39.4 ± 3.9 min) and higher C max (0.57 ± 0.02 μg/mL) compared to ASA. These pharmacokinetic parameters showed that 3-CH 2 Cl is widely and deeply distributed in all body tissues, yielding a slower onset of action and longer elimination time compared to ASA [9]. Moreover, our studies on in vitro human platelet aggregation studies postulated the mechanism of antiplatelet activity of 3-CH 2 Cl, by inhibiting COX-1.…”
Section: Introductionmentioning
confidence: 63%
“…Our group recently synthesized a new compound derived from salicylic acid, namely 2-((3-(chloromethyl)benzoyl)oxy)benzoic acid (3-CH 2 Cl) that has the benefits of acetylsalicylic acid but lacks its harmful side effects [9]. The analgesic and anti-platelet activity of 3-CH 2 Cl wa s administered in normal Wistar rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation